2013
DOI: 10.7897/2277-4572.02457
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Toxic Effects of Prolonged Intake of Cassava-Borne Organic Cyanide and Inorganic Cyanide in Some Rabbit Tissues

Abstract: The study was aimed at comparing the toxic effects of cassava-borne organic cyanide and equivalent level of inorganic cyanide (KCN) in New Zealand White rabbits. Three groups of 3-month old, male weanling rabbits (4 per group) were used. One group received pure growers mash (control), while another was fed isonitrogenous cassava peel flour, CPF containing 702 ppm organic cyanide. A third group was given mash with 702 ppm KCN (inorganic cyanide). Feed intake, body weight gain, and serum SCN-were recorded. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Based on the results of this experiment and previous studies it can be suggested that the use of YEFECAR as the primary source of protein in concentrate feed has a tendency to cause lower levels of DM intake. This may be connected with the chemical composition of YEFECAR, which contains approximately 47.3 mg/kg of HCN (Boonnop et al, 2009) that contributes to loss of appetite in animals Microbial N (gN/d) = X (mmol/d) × 70 0.116 × 0.83 × 1000 (Paulinus and Obaika, 2013). In addition, the presence of HCN in ruminant feed leads to higher levels of sulphur intake or sulphur-containing amino acids such as methionine and cysteine, for HCN detoxification (Promkot et al, 2007;Promkot and Wanapat, 2009;Cherdthong et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of this experiment and previous studies it can be suggested that the use of YEFECAR as the primary source of protein in concentrate feed has a tendency to cause lower levels of DM intake. This may be connected with the chemical composition of YEFECAR, which contains approximately 47.3 mg/kg of HCN (Boonnop et al, 2009) that contributes to loss of appetite in animals Microbial N (gN/d) = X (mmol/d) × 70 0.116 × 0.83 × 1000 (Paulinus and Obaika, 2013). In addition, the presence of HCN in ruminant feed leads to higher levels of sulphur intake or sulphur-containing amino acids such as methionine and cysteine, for HCN detoxification (Promkot et al, 2007;Promkot and Wanapat, 2009;Cherdthong et al, 2018).…”
Section: Resultsmentioning
confidence: 99%